SOFT SKILL, HARD SKILL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA RBTV KOTA BENGKULU - Adi Sismanto; Peri Yusrizal (UM. Bengkulu, 2023)
This study aims to find out the influence of soft skills, hard skills and motivation on employee performance at RBTV Bengkulu City. The population of this study was all RBTV employees numbering 50 people. All of those employees were sampled for research. Data collection techniques with questionnaires and data analysis techniques using regression. The results of this study revealed that soft skills have a significant effect on employee performance, hard skills have a significant effect on employee performance and motivation has a significant effect on employee performance at RBTV Bengkulu City. Keywords: soft skills, hard skills, motivation and performance.